Motives for romantic relationships and the risk of heavy alcohol use, regular smoking and cannabis use during adolescence and early adulthood: a longitudinal study - Liang, Wenbin; Chikritzhs, Tanya (Scientific Research Publishing Inc, 2013)
BACKGROUND: Engaging in sexual activities at a younger age is associated with higher risk of substance misuse among adolescents. It could be hypothesized that substance misuse and certain romantic relationship related behaviors may be influenced by similar hormone and other inner physiological factors that are affected by related motives. This study investigated the association between motives for romantic relationships and the risk of heavy alcohol use, regular smoking and cannabis use from adolescence through to early adulthood.METHOD: A population-based longitudinal study using data collected from Wave I and Wave III of the National Longitudinal Study of Adolescent Health. Characteristics of romantic relationship ideals (as the proxy of motives) measured in Wave I (mean age: 16 yrs) were applied to predict substance use indicated at Wave III (mean age: 22 yrs) using multivariate analyses.RESULTS: Adolescents who included sexual activities as part of their romantic relationship ideals were at significantly higher risk of cannabis use among males and heavy alcohol use among females. Romantic ideals that included, gift giving (female) or receiving (male), declaration of love (male), marriage (male) and becoming pregnant (female) were associated with reduced risk of one or more types of substance use.CONCLUSION: In adolescence, sexual motives for romantic relationships were associated with higher risk of substance use and misuse, while motives related to intimacy and commitment in romantic relationships were associated with lower risk.